Shantyboat on the bayous - Hubbard, Harlan (University Press of Kentucky, 1990)
Since the publication of Shantyboat: A River Way of Life in 1953, Harlan Hubbard achieved a wide reputation as a modern-day Thoreau. Not content simply to advocate a life of simplicity and self-sufficiency, Hubbard and his wife Anna in 1944 built with their own hands a houseboat on the banks of the Ohio near Cincinnati and in 1946 set out on a leisurely, five-year journey down the Ohio and Mississippi rivers. Shantyboat, Hubbard's recounting of their journey to New Orleans, and Payne Hollow: Life on the Fringe of Society, his sequel telling of their life in a corner of rural Kentucky after.